Menstrual Equity, Organizing and the Struggle for Human Dignity and Gender Equality in Prison - Fettig, Amy (Columbia Journal of Gender and Law, 2021)
This Essay takes a look at the movement for social change around menstruation, especially through the lens of the criminal legal system and prisons and jails in particular. Part I reviews the issues of period poverty and justice that are driving a larger social movement to recognize that safe and ready access to menstrual hygiene products should be framed through a lens of full civic participation in order to understand its full implications for the lives of people who menstruate. Part II dives into the particular needs and problems of abuse and control that incarcerated and detained people face related to menstruation. Part III examines the growing movement to transform menstruation in America along equity lines that focuses both on the rights of all menstruators while bringing social pressure to bear on behalf of the most vulnerable—incarcerated people, the unhoused, students, and those living in poverty—to demand greater governmental and cultural support for the needs, inclusion, and dignity of all people who menstruate. This Part particularly takes note of the fact that the menstrual equity movement gains strength and force when it centers the leadership and voices of people who menstruate as key players demanding social change and evolution of the culture as a whole. Part IV examines the importance of the momentum and success this social movement represents for potential litigation strategies to develop constitutional jurisprudence regarding incarcerated people and menstrual equity. It observes that the pertinent “evolving standards of decency” that inform Eighth Amendment jurisprudence must and will be influenced by the prevailing movement for menstrual equity as a deliberate strategy to ensure that incarcerated people who menstruate are not left out of the social development and rights framework that menstrual equity demands. At the same time this evolution in jurisprudence represent the opportunity for Eighth Amendment jurisprudence—and constitutional framework generally—to place a greater focus on the need for human dignity as a cornerstone of the law.